2015
DOI: 10.1039/c5ra09047d
|View full text |Cite
|
Sign up to set email alerts
|

Superior methanol electrooxidation activity and CO tolerance of mesoporous helical nanospindle-like CeO2modified Pt/C

Abstract: In an attempt to enhance the electrocatalytic activity and CO tolerance of ceria modified Pt/C electrodes, a novel structured ceria material has been developed. Left-handed helical CeO 2 nano-spindles with mesoporous structures were successfully synthesized through a template-free based precursor method on a large scale. By a microwave-assisted polyol synthesis process, the ceria modified Pt/C electrocatalysts were synthesized. The helical CeO 2 nanospindle based electrode Pt@Heli-CeO 2 /C exhibits superior el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The OH species can oxidize the -CO species adsorbed on the surface of the neighboring Pt atoms to CO2 and, thus, increase the CO tolerance of Pt. Besides the metal promoters, metal oxides, such as SnO2 and CeO2, have also been used as effective promoters for Pt catalysts owing to the low cost and easily tunable surface properties by straightforward synthesis procedures [4][5][6]. Xing et al [4] reported that Sb-doped SnO2 could not only act as an effective promoter but also act as a favorable support for Pt catalysts owing to the high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The OH species can oxidize the -CO species adsorbed on the surface of the neighboring Pt atoms to CO2 and, thus, increase the CO tolerance of Pt. Besides the metal promoters, metal oxides, such as SnO2 and CeO2, have also been used as effective promoters for Pt catalysts owing to the low cost and easily tunable surface properties by straightforward synthesis procedures [4][5][6]. Xing et al [4] reported that Sb-doped SnO2 could not only act as an effective promoter but also act as a favorable support for Pt catalysts owing to the high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous study, we employ L-aspartic acid sodium through a soft-chemistry based one-step hydrothermal reaction with a variety of lanthanide nitrate hexahydrates to generate hierarchical RBC-like macroparticles. 37 Ln(OH)CO 3 , with chiral architectures, can be prepared through a biomimetic selfassembly approach and exhibit characteristic CD responses in the UV-visible absorption region due to electron transition-based optical activity (ETOA).…”
mentioning
confidence: 99%